COMPARTMENTAL MODELING APPROACH OF LOSARTAN TRANSDERMAL TRANSPORT IN VITRO - Nugroho, Akhmad Kharis (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2014)
Development of losartan in transdermal formulation is important due to its low oral bioavailability. Optimal transdermal formulation requires transport mechanism understanding. This study was aimed to develop and evaluate compartmental modeling of losartan transdermal transport in vitro to fulfil this demand. Losartan solution (10g/L in 20% propylene glycol) was filled into the acceptor phase of a vertical diffusion-cells system. The fresh rat skin (pretreated with oleic acid for 1 hour) was used as the transport membrane separating the donor and the acceptor phase, which was filled with phosphate-buffered-saline pH 7.4. During 30h, samples were collected and analyzed using HPLC method. Four compartmental models were proposed, i.e. models with one (model 1) or two (model 2) lag-compartment(s) either with a zero-order (model A) or a first- order (model B) drug input from donor to the skin. WinSAAM was used to evaluate the models based on the parameters: 1) visual goodness of fit (GOF); and 2) Corrected Akaike's Information Criterion (AICc). Both the GOF and AICc evaluations indicated model 2-A as the best model describing losartan transdermal transport. The model suggested that after reaching the upper layer of skin at a constant rate, losartan transport was split into two flows. Both flows are transited in two separate lag-compartments before reaching into the acceptor phase.Key words: Transdermal, Losartan, Modeling, Lag-compartment, WinSAAM